2019
DOI: 10.1101/767665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Resolution Structural Insights into Heliorhodopsin Family

Abstract: Rhodopsins are the most abundant light-harvesting proteins. A new family of rhodopsins, heliorhodopsins (HeRs), was recently discovered. In opposite to the known rhodopsins their N-termini face the cytoplasm. HeRs structure and function remain unknown. We present structures of two HeR-48C12 states at 1.5 Å showing its remarkable difference from all known rhodopsins. Its internal extracellular part is completely hydrophobic, while the cytoplasmic part comprises a cavity ('active site'), surrounded by charged am… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 61 publications
1
21
1
Order By: Relevance
“…While the biological function of HeRs remains unknown, thorough study of different 48C12 states is of great potential benefit for elucidating it. To investigate A B the conformational rearrangements in the HeR associated with pH decrease, we also solved the crystal structure of 48C12 at 1.5 Å using the crystals grown at pH 4.3 (36). Indeed, pH of the surrounding solution affects the functionality and the structure of microbial rhodopsins due to protonation or deprotonation of the key residues (37-39).…”
Section: Resultsmentioning
confidence: 99%
“…While the biological function of HeRs remains unknown, thorough study of different 48C12 states is of great potential benefit for elucidating it. To investigate A B the conformational rearrangements in the HeR associated with pH decrease, we also solved the crystal structure of 48C12 at 1.5 Å using the crystals grown at pH 4.3 (36). Indeed, pH of the surrounding solution affects the functionality and the structure of microbial rhodopsins due to protonation or deprotonation of the key residues (37-39).…”
Section: Resultsmentioning
confidence: 99%
“…S5). HeRs from the monophyletic group A (subfamily 1 in (Kovalev et al 2020)) are represented mostly by proteins from Actinobacteria, including HeR-48C12 and several of the clones reported here, while group B is more diverse and includes Bc HeR (Chloroflexi) and…”
Section: Resultsmentioning
confidence: 76%
“…Notice however that reminiscently of the DegV proteins, the crystal structures of HeRs revealed that they bind such lipids from the membranes used for crystallization as the FA monooleate and the alkane eicosane and that the corresponding binding site is localized to the fenestration that exposes the β-ionone ring of the retinal moiety (Shihoya et al 2019, Kovalev et al 2020. Taken together, these observations are suggestive of HeRs participating in FA modification in a light-dependent manner.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Identified during a functional metagenomics screen and characterised by low sequence similarity when compared to type-1 rhodopsins, HeRs attracted increasing research interest due to their peculiar membrane orientation (i.e. N-terminus in the cytoplasm and the C-terminus in the extracellular space) (Pushkarev et al 2018), unusual protein structure (Kovalev et al 2020) and controversial taxonomic distribution (Flores-Uribe, Hevroni, and Ghai 2019). While electrophysiological (Pushkarev et al 2018), physicochemical (Tanaka et al 2020) and structural (Shihoya et al 2019;Kovalev et al 2020) studies achieved great progress in elucidating a series of characteristics ranging from photocycle length (indicating no pumping activity) to detailed protein organization, they provide no data regarding the biological function of HeRs.…”
mentioning
confidence: 99%